The Integration of Tawakal Values in Islamic Religious Education Learning: A Conceptual Analysis of the Al-Hikam Perspective by Ibn Athaillah al-Sakandari - Fudailah Alfain; Sinta Nuriyah; Mohammad Wakhyudi; Zamach Syari; Ahmad Syifauddin; Moch. Mahdiyan Nasikhin; Meylinda Khusnan Aprilia; Siti Khafiyatul Ulwiyah; M. Husni Mubarak (Universitas Muhammadiyah Enrekang, 2026)
This research aims to reconstruct the concept of tawakal in the perspective of the book Al-Hikam by Ibn Athaillah al-Sakandari and formulate its integration in the learning of Islamic Religious Education (PAI). In the modern era, the distortion of understanding of tawakal often gives birth to a fatalistic (passive) attitude or conversely, rationality without a spiritual dimension that triggers anxiety. Using qualitative methods through library research and philosophical-pedagogical approaches, this study analyzes the content of the book of Al-Hikam as a primary source. The findings of the study show that in Ibn Athaillah's view, tawakal is not a passive attitude, but a balance between submission of the heart (the inner aspect) and obedience in endeavor (the birth aspect). Pedagogically, tawakal values can be integrated into PAI learning through the internalization of character values, teacher examples, and reflective processes. This integration functions as an instrument of emotional regulation for students, which is parallel to the concepts of self-efficacy and perceived control in psychology, so as to be able to form a student mentality that is resilient, optimistic, and has inner peace in facing academic and social challenges